Experiential Marketing and Electronic Word of Mouth on Consumer Loyalty Through Consumer Satisfaction at Jember Mini Zoo Tourist Attraction - Vidia Yunita Kurnia; Diah Yulisetiarini; Bambang Irawan (International Journal of Management Research and Economics, 2024)
The purpose of this study was to determine the role of satisfaction in mediating the influence of experiential marketing and electronic word of mouth on consumer loyalty through consumer satisfaction at the Jember Mini Zoo tourist attraction. This study uses explanatory research. The population in this study were visitors to the Jember Mini Zoo tourist attraction. The method used in this study was purposive sampling. The age of respondents in this study was at least 18 years old with the consideration that this age can make wise decisions. Respondents were visitors to the Jember Mini Zoo tourist attraction at least 2 times. The sample size in this study was 14 x 10 = 140 respondents. The data analysis method used Structural Equation Modeling (SEM) with the Amos application. The results showed that Experiential marketing on satisfaction showed a significant positive effect. Electronic word of mouth on Satisfaction showed a significant positive effect. Experiential marketing on consumer loyalty showed a significant positive effect. Electronic word of mouth on consumer loyalty showed a significant positive effect. Consumer satisfaction on consumer loyalty showed a significant positive effect. Experiential marketing on consumer loyalty through consumer satisfaction showed a significant positive effect. Electronic word of mouth on consumer loyalty through consumer satisfaction shows a significant positive influence.